Hyperglycemia and Cardiovascular Risk in Diabetes mellitus Type 1 and Diabetes mellitus Type 2 - Zander, E.; Kohnert, K.-D.; Allwardt, Chr.; Reindel, J.; Schmidt, J.; Kerner, W.; Motz, W. (Fundamental and Experimental Biology, 2016)
Diabetes mellitus is a chronic disease that through its complications seriously reduces quality of life and life expectancy in diseased people. There is a worldwide increase in the prevalence in diabetes mellitus type 2. Our understanding in reducing the micro- and macrovascular risk has increased in the last time. But, in contrast to microvascular morbidity the most persistent menace to the health in diabetic patients of both types remains atherosclerosis with increased cardiovascular morbidity and mortality when compared with the non-diabetic population. In the past, the role of hyperglycemia on CVD was not completely elucidated. It was the aim to review and to compare the role of hyperglycemia on cardiovascular morbidity and mortality both in type 2 and type 1 diabetes. Results from ADVANCE and UKPDS Studies in type 2 diabetes have shown that the effect of intensive glucose control was associated with decreased risk of cardiovascular disease and death from any cause in addition to reduction of microvascular disease. HbA1c targets lower than 7.5 % and near to 6.5 % and avoiding of hypoglycemia are recommended. DCCT-EDIC Study data in type 1 diabetes have demonstrated that an early intensive metabolic control near to normal level initiated in patients with short diabetes duration and without microangiopathic complications such as nephropathy significantly reduced micro- and macrovascular morbidity. The long lasting effect of intensive control is called «memory effect». Near normal HbA1c levels at least < 7.5 % and individually targeted in order to avoid hypoglycemia are required. When comparing both types of diabetes, in type 1 as well as type 2 diabetes intensified glucose control resulted in long-lasting effects, reducing significantly cardiovascular morbidity and mortality. Treatment has to be initiated early in the course of the disease. But considering meta-analyses of large randomized controlled trials of intensive vs. conventional glycemiccontrol in type 2 diabetes, hyperglycemia has shown to be a weaker cardiovascular risk factor than increased cholesterol levels or hypertension.